Method for in-situ electrochemical activation of an anode material

CN123017848APending Publication Date: 2026-10-30GUANGXI UNIV FOR NATITIES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610979238.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]鉴于此,本发明提出了一种原位电化学活化制备正极材料的方法,旨在解决当前技术中电池材料过程中存在生产流程冗长低效、综合成本高、难以规模化生产的问题

Benefits of technology

本发明通过前驱体制备、电池组装、原位电化学活化一体化流程,相较于现有技术材料离线多步制备、电池组装的模式,省去多项后处理步骤,总制备时间缩短,生产效率得到提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of battery materials, and discloses a method for preparing a positive electrode material through in-situ electrochemical activation, which comprises the following steps: preparing a composite precursor, assembling a battery, and performing step-by-step electrochemical activation; under the action of a nitrogen-containing precursor in an electrolyte, carboxylation, nitrogen doping and cyclodextrin fixation are simultaneously realized through a step-by-step electrochemical procedure, so that a cyclodextrin-nitrogen-doped multi-walled carbon nanotube positive electrode material is formed in-situ. The preparation method disclosed by the application not only significantly improves the charging polarization and self-discharge performance of a zinc-bromine static battery, but also greatly simplifies the process and reduces the cost, the cost is reduced by more than 30%, the charging polarization is effectively reduced, the self-discharge is inhibited, the battery performance is excellent, and the process is stable and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and more specifically, to a method for preparing cathode materials through in-situ electrochemical activation. Background Technology

[0002] Based on the cost and performance requirements of the large-scale energy storage market for zinc-bromine static batteries, the existing technology CN119764469A patent discloses a cyclodextrin-nitrogen-doped multi-walled carbon nanotube (CD-NCNTs) cathode material, prepared by a three-step method of nitrogen doping by ammonia calcination → carboxylation with a strong oxidant → esterification and fixation with cyclodextrin. Although this method can solve the core problems of large charging polarization and self-discharge in zinc-bromine static batteries, it has significant bottlenecks in practical industrial applications: 1) The existing technology requires independent multi-step offline processing, including calcination in an ammonia atmosphere requiring 6-10 hours, condensation and reflux oxidation with a strong oxidant requiring 6-12 hours, and subsequent washing and drying processes totaling 24-32 hours. The entire material preparation cycle is as long as 40-54 hours, which seriously restricts production. Efficiency; 2) In terms of raw materials, it requires the consumption of ammonia (a hazardous gas with high procurement and storage costs), potassium permanganate, or concentrated nitric acid and other strong oxidants (highly corrosive and expensive); in terms of equipment, it relies on multiple high-energy-consuming equipment such as tubular furnaces, condenser reflux devices, and vacuum dryers; in terms of environmental protection, the strong oxidant washing process will generate a large amount of acidic wastewater, and subsequent treatment requires additional investment costs, making it difficult to reduce the overall production cost; the multi-step post-processing process has strict requirements for process parameter control, such as the calcination temperature needs to be precisely maintained at 300-450℃, the ammonia flow rate needs to be controlled at 20-25mL / min, and the condenser reflux speed needs to be stable at 1000-1200rpm, etc. Parameter fluctuations can easily lead to batch differences in material performance, increasing the difficulty of control in large-scale production.

[0003] Therefore, developing a cathode material preparation technology that is simplified in process, controllable in cost, and adaptable to large-scale production is of great practical significance. Summary of the Invention

[0004] In view of this, the present invention proposes a method for preparing cathode materials by in-situ electrochemical activation, which aims to solve the problems of lengthy and inefficient production processes, high overall costs, and difficulty in large-scale production in the current battery material process.

[0005] This invention proposes a method for preparing cathode materials through in-situ electrochemical activation, comprising the following steps: (1) Preparation of precursor: Multi-walled carbon nanotubes, cyclodextrin, XC-72 conductive carbon and polytetrafluoroethylene are mixed, isopropanol is added to make slurry, pressed into thin sheets, and dried at room temperature to obtain composite precursor cathode. (2) Assemble the battery: The composite precursor is used as the positive electrode, zinc foil is used as the negative electrode, microporous membrane is used as the separator and electrolyte is sealed to obtain the assembled battery; (3) In-situ electrochemical activation: A step-by-step electrochemical activation procedure is performed at room temperature. The step-by-step electrochemical activation includes a first stage, a second stage and a third stage. The first stage is pre-activation, the second stage is cyclic activation, and the third stage is sizing activation. After activation, a positive electrode material is formed in situ at the positive electrode.

[0006] Furthermore, in step (1), the multi-walled carbon nanotubes, cyclodextrin, XC-72 conductive carbon, and polytetrafluoroethylene are mixed in a mass ratio of 80-85:10-15:3-5:2-5.

[0007] Furthermore, the cyclodextrin mentioned in step (1) is one or more of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-α-cyclodextrin, hydroxyethyl-β-cyclodextrin, and hydroxypropyl-γ-cyclodextrin.

[0008] Furthermore, the amount of isopropanol added in step (1) is 8 to 15 times the total mass of solids; the slurry preparation parameters are: rotation speed 400 to 800 r / min, time 20 to 40 min, and temperature 20 to 30 °C.

[0009] Furthermore, in step (1), the thickness of the sheet is 0.1~0.3mm; the room temperature drying time is 2~4h.

[0010] Furthermore, the electrolyte in step (2) contains 1-3 mol / L ZnBr2 aqueous solution and 0.5-1 mol / L nitrogen-containing precursor; the nitrogen-containing precursor is urea or melamine.

[0011] Furthermore, the room temperature mentioned in step (3) is 20~30℃.

[0012] Furthermore, the pre-activation parameters in step (3) are: potential 1.0~1.4V and time 1.5~4h.

[0013] Furthermore, the cyclic activation parameters in step (3) are: potential 0.7~1.7V, number of cycles 8~22, and scan rate 3-15mV / s.

[0014] Furthermore, the activation parameters in step (3) are: potential 1.7~1.9V and time 0.8~2.5h.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention integrates precursor preparation, battery assembly, and in-situ electrochemical activation into a single process. Compared to existing technologies that involve offline multi-step material preparation and battery assembly, this process eliminates multiple post-processing steps, shortens the overall preparation time, and improves production efficiency.

[0016] This invention achieves a three-step reaction—carboxylation, nitrogen doping, and cyclodextrin immobilization—in situ through a specific electrochemical procedure. This results in a more uniform distribution of pyridine nitrogen catalytic sites and a stronger bond between cyclodextrin and carbon nanotubes, enabling efficient enrichment of Br. - / Br3 - It also accelerates the redox of bromine species, significantly reduces charging polarization, and suppresses self-discharge.

[0017] The entire process of this invention is carried out under mild conditions, without high temperature, high pressure, or strong corrosive operations, and without the emission of toxic gases or the generation of acidic waste liquid. The production process is safer and more environmentally friendly, meeting the requirements for the manufacture of green energy storage materials.

[0018] This invention precisely controls the reaction using only electrochemical parameters, without the presence of complex variables such as sensitive temperature field, gas velocity, and stirring speed. It achieves high batch consistency and can be directly programmed for automated execution, significantly reducing the difficulty of controlling large-scale production.

[0019] In this invention, the preparation of the cathode material and the first activation of the battery are completed simultaneously. After activation, the battery can be put into use directly without disassembling the battery, changing materials, or reassembling it. This truly realizes that assembly is preparation and activation is forming, which greatly shortens the manufacturing cycle of zinc-bromine static batteries. Detailed Implementation

[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.

[0021] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0022] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0023] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0024] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0025] This invention provides a method for preparing cathode materials through in-situ electrochemical activation, comprising the following steps: (1) Preparation of precursor: Multi-walled carbon nanotubes, cyclodextrin, XC-72 conductive carbon and polytetrafluoroethylene are mixed, isopropanol is added to make a slurry, pressed into a thin sheet, and dried at room temperature to obtain a composite precursor cathode. (2) Assemble the battery: Seal the composite precursor as the positive electrode, zinc foil as the negative electrode, microporous membrane as the separator and electrolyte to obtain the assembled battery; (3) In-situ electrochemical activation: A step-by-step electrochemical activation procedure is performed at room temperature. The step-by-step electrochemical activation includes a first stage, a second stage and a third stage. The first stage is pre-activation, the second stage is cyclic activation, and the third stage is sizing activation. After activation, a positive electrode material is formed in situ at the positive electrode.

[0026] In this invention, the multi-walled carbon nanotubes, cyclodextrin, XC-72 conductive carbon and polytetrafluoroethylene mentioned in step (1) are preferably mixed in a mass ratio of 80-85:10-15:3-5:2-5, and more preferably in a mass ratio of 82-85:10-14:3-4:2-4.

[0027] In this invention, the cyclodextrin mentioned in step (1) is one or more of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-α-cyclodextrin, hydroxyethyl-β-cyclodextrin, and hydroxypropyl-γ-cyclodextrin.

[0028] In this invention, the amount of isopropanol added in step (1) is preferably 8 to 15 times the total mass of solids, and more preferably 10 to 15 times; the slurry preparation parameters are preferably: rotation speed 400 to 800 r / min, time 20 to 40 min, temperature 20 to 30 °C, and more preferably rotation speed 500 to 800 r / min, time 25 to 40 min, temperature 23 to 30 °C.

[0029] This invention adds isopropanol to the precursor preparation. The isopropanol can disperse carbon nanotubes, cyclodextrin, and conductive carbon powder, break up particle agglomeration, and achieve uniform mixing of raw materials. It can reasonably control the fluidity and consistency of the paste, adapt to the rolling process, and facilitate the pressing of electrode sheets of uniform thickness. It can also slowly volatilize at room temperature, leaving no residue during the drying process, without damaging the structure of the precursor components, without affecting the subsequent electrochemical activation reaction, and can penetrate and wet the gaps between powders, reducing internal pore defects of the electrode and ensuring the continuous and stable conductive network of the electrode.

[0030] This invention uses isopropanol as a slurry preparation medium in the preparation of the precursor. This slurry, using isopropanol as the dispersion medium, fully disperses multi-walled carbon nanotubes, cyclodextrin, conductive carbon, and binders, eliminating powder agglomeration and ensuring uniform mixing of all components. It can control the viscosity and flowability of the slurry, adapting it to the film-forming process and facilitating the pressing of precursor sheets with uniform thickness and smooth surfaces. Furthermore, it enhances the bonding between the powder and tetrafluoroethylene, strengthening the overall structural strength of the electrode and preventing electrode detachment and pulverization during subsequent activation and charge-discharge processes. Simultaneously, it ensures uniform distribution of electrode components, allowing subsequent in-situ electrochemical activation reactions to proceed uniformly, ensuring consistent nitrogen doping and cyclodextrin fixation effects, and stabilizing the battery's electrochemical performance. In this invention, the thickness of the sheet in step (1) is preferably 0.1~0.3mm, more preferably 0.15~0.3mm; the room temperature drying time is preferably 2~4h, more preferably 2.5~4h.

[0031] In this invention, the electrolyte in step (2) is preferably composed of 1-3 mol / L ZnBr2 aqueous solution and 0.5-1 mol / L nitrogen-containing precursor, and more preferably composed of 1.5-3 mol / L ZnBr2 aqueous solution and 0.6-1 mol / L nitrogen-containing precursor; the nitrogen-containing precursor is urea or melamine.

[0032] This invention employs a method for preparing cathode materials through in-situ electrochemical activation, utilizing a nitrogen-containing precursor for direct battery assembly. The precursor, comprising urea or melamine, provides active nitrogen species through electrochemical decomposition, enabling the in-situ construction of pyridine nitrogen catalytic sites on the surface of multi-walled carbon nanotubes. This provides an active nitrogen source, achieving in-situ nitrogen doping, maintaining electrolyte stability, promoting cyclodextrin fixation, regulating the reaction environment, and synergistically enhancing functional performance. Furthermore, the in-situ generation of pyridine nitrogen catalytic sites accelerates Br₂… - Oxidation reaction reduces the charge-discharge voltage difference, and nitrogen doping can be achieved directly in the electrolyte without the need for ammonia calcination, thus reducing overall costs.

[0033] Furthermore, the nitrogen-containing precursor is the key material for achieving in-situ nitrogen doping in this invention. Its role is not only to provide a nitrogen source, but also to regulate the reaction environment through electrochemical decomposition products, forming a synergistic effect with cyclodextrin fixation, and ultimately achieving the simultaneous solution of battery charging polarization and self-discharge problems.

[0034] In this invention, the room temperature in step (3) is preferably 20~30℃, and more preferably 23~30℃.

[0035] In this invention, the pre-activation parameters in step (3) are preferably: potential 1.0~1.4V and time 1.5~4h, and more preferably potential 1.1~1.4V and time 2~4h.

[0036] This invention employs pre-activation in the in-situ electrochemical activation process. The pre-activation stage is the initiation of the reaction for preparing the cathode material and the construction of basic sites. By applying a constant potential, under the influence of the electric field of the two-electrode system, an electrochemical oxidation reaction (CNTs react with H₂O-2e⁻) occurs on the surface of the multi-walled carbon nanotubes (CNTs) in the composite precursor. - →CNTs-COOH and 2H + This introduces oxygen-containing groups such as carboxyl groups (-COOH) onto the surface of CNTs. These carboxyl groups serve as the linking sites for subsequent esterification reactions with the hydroxyl groups in cyclodextrin molecules.

[0037] Furthermore, the potential field simultaneously drives the electrochemical decomposition of nitrogen-containing precursors (urea / melamine) in the electrolyte. Urea decomposes to generate NH3, CO2, and nitrogen free radicals (·NH2), while melamine decomposes to generate melamine free radicals and nitrogen free radicals. These nitrogen free radicals are the active nitrogen source for subsequent nitrogen doping, providing the material basis for the formation of pyridine nitrogen. At the same time, a mild potential is used to avoid excessively high potentials that could lead to Br in the electrolyte. - Premature oxidation to generate Br2, or excessively low potential preventing the reaction from starting, ensures that carboxyl group formation and nitrogen precursor decomposition proceed synchronously and smoothly.

[0038] In this invention, the cyclic activation parameters in step (3) are preferably: potential 0.7~1.7V, number of cycles 8~22, and scan rate 3-15mV / s, and more preferably potential 0.8~1.7V, number of cycles 10~22, and scan rate 5-15mV / s.

[0039] This invention employs cyclic activation in the in-situ electrochemical activation process. During the cyclic activation, the electric field intensity periodically changes as the cyclic potential scans repeatedly in the low-potential range. This promotes the binding of nitrogen free radicals (·NH₂) generated in the pre-activation stage to defect sites on the CNT surface, forming stable pyridine nitrogen (CN bonds). The dynamic process of cyclic scanning ensures a more uniform distribution of nitrogen free radicals on the CNT surface, avoiding localized over- or under-doping of nitrogen, ultimately leading to the formation of a highly efficient catalytic Br₂. - Oxidized pyridine nitrogen sites solve the charging polarization problem; the carboxyl groups (-COOH) generated on the CNT surface and the hydroxyl groups (-OH) in the cyclodextrin molecule undergo esterification under an electric field (CNTs-COOH and HO-CD → CNTs-OOC-CD and H2O). The cyclic potential provides a continuous energy input for the esterification reaction, while promoting full contact between unreacted carboxyl groups and hydroxyl groups, improving the cyclodextrin fixation rate. The fixed cyclodextrin molecules specifically enrich Br through their hydrophobic cavities. - / Br3 - This lays the structural foundation for subsequent suppression of self-discharge; the scanning rate controls the reaction rate: too slow a rate will lead to low reaction efficiency and prolonged total time; too fast a rate will lead to insufficient reaction; the number of cycles used ensures that nitrogen doping and esterification reactions reach a dynamic balance, which ensures the number of functional sites and avoids excessive reaction that could damage the material structure.

[0040] In this invention, the shaping and activation parameters in step (3) are preferably: potential 1.7~1.9V and time 0.8~2.5h, and more preferably potential 1.7~1.8V and time 0.8~2h.

[0041] This invention employs a type-fixed activation process during in-situ electrochemical activation. This type-fixed activation utilizes a slightly higher potential to further drive the binding of residual nitrogen radicals to CNTs, while simultaneously increasing the binding energy between the formed pyridine nitrogen sites and the CNT matrix. This prevents nitrogen atom loss during cyclic charge-discharge cycles, ensuring the long-term stability of the catalytic sites. The continuous constant potential ensures a more complete esterification reaction, allowing unreacted carboxyl and hydroxyl groups to continue reacting, while inhibiting ester bond hydrolysis. This results in a stronger bond between cyclodextrin and CNTs, preventing cyclodextrin dissolution in the electrolyte from causing bromine enrichment failure. At a slightly higher potential, a slight electrochemical reconstruction occurs on the surface of the cathode material, more fully exposing the pyridine nitrogen catalytic sites and cyclodextrin enrichment structures, thus enhancing Br… - This improves mass transfer efficiency and reactivity, further reducing charging polarization. Simultaneously, this potential is below the critical decomposition potential of the ZnBr2 electrolyte, preventing electrolyte failure.

[0042] This invention employs in-situ electrochemical activation in the preparation of cathode materials. The process involves pre-activation to generate carboxyl and nitrogen free radicals, followed by cyclic activation for nitrogen doping and cyclodextrin fixation, and final activation to solidify the structure and optimize performance, forming a complete reaction chain. The potential is gradually adjusted from a gentle start-up at a low potential to a dynamic reaction at a medium potential, and finally to enhanced stability at a slightly higher potential, matching the energy requirements of each stage of the reaction and avoiding insufficient or excessive reactions caused by a single potential. The resulting pyridine nitrogen catalytic sites and cyclodextrin-enriched structures work synergistically to address the core problems of large charging polarization and self-discharge in zinc-bromine static batteries. This three-stage stepped design is the key guarantee for achieving this synergistic function.

[0043] In this invention, a method for preparing cathode materials through in-situ electrochemical activation is used to prepare a zinc-bromine static battery cathode, wherein the active component of the cathode is an in-situ formed cyclodextrin-nitrogen-doped multi-walled carbon nanotube.

[0044] In this invention, unless otherwise specified, all raw materials required for preparation are commercially available products well known to those skilled in the art.

[0045] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0046] Example 1 (1) Preparation of precursor: Multi-walled carbon nanotubes, α-cyclodextrin, XC-72 conductive carbon and polytetrafluoroethylene were mixed in a mass ratio of 82:10:4:4. Isopropanol with a mass ratio of 10 times the total solid mass was added and the mixture was slurried at 500 r / min and 23℃ for 40 min. The mixture was then pressed into 0.15 mm thin sheets and dried at room temperature for 2.5 h to obtain the composite precursor cathode. (2) Assemble the battery: Seal the composite precursor as the positive electrode, zinc foil as the negative electrode, microporous membrane as the separator and an electrolyte consisting of a mixture of 1.5 mol / L ZnBr2 aqueous solution and 0.6 mol / L urea to obtain the assembled battery; (3) In-situ electrochemical activation: A step-by-step electrochemical activation procedure is performed at 23°C, including pre-activation (1.1V, 4h), cyclic activation (0.8V, 22 cycles, scan rate 8mV / s), and shaping activation (1.7V, 2h). After activation, positive electrode material is formed in situ at the positive electrode.

[0047] Example 2 (1) Preparation of precursor: Multi-walled carbon nanotubes, α-cyclodextrin, XC-72 conductive carbon and polytetrafluoroethylene were mixed in a mass ratio of 82:10:4:4. Isopropanol with a mass ratio of 10 times the total solid mass was added and the mixture was slurried at 500 r / min and 23℃ for 40 min. The mixture was then pressed into 0.15 mm thin sheets and dried at room temperature for 2.5 h to obtain the composite precursor cathode. (2) Assemble the battery: Seal the composite precursor as the positive electrode, zinc foil as the negative electrode, microporous membrane as the separator and an electrolyte consisting of a 2 mol / L ZnBr2 aqueous solution and 0.8 mol / L melamine to obtain the assembled battery; (3) In-situ electrochemical activation: A step-by-step electrochemical activation procedure is performed at 23°C, including pre-activation (1.1V, 3h), cyclic activation (0.8V, 20 cycles, scan rate 5mV / s), and shaping activation (1.7V, 2h). After activation, positive electrode material is formed in situ at the positive electrode.

[0048] Example 3 (1) Preparation of precursor: Multi-walled carbon nanotubes, β-cyclodextrin, XC-72 conductive carbon and polytetrafluoroethylene were mixed in a mass ratio of 83:12:3:2. Isopropanol with a mass ratio of 12 times the total solid mass was added and the mixture was slurried at 600 r / min and 25℃ for 30 min. The mixture was pressed into 0.2 mm thin sheets and dried at room temperature for 3 h to obtain the composite precursor cathode. (2) Assemble the battery: Seal the composite precursor as the positive electrode, zinc foil as the negative electrode, microporous membrane as the separator and an electrolyte consisting of a mixture of 2.5 mol / L ZnBr2 aqueous solution and 0.8 mol / L urea to obtain the assembled battery; (3) In-situ electrochemical activation: A step-by-step electrochemical activation procedure is performed at 25°C, including pre-activation (1.2V, 3.5h), cyclic activation (1V, 15 cycles, scan rate 6mV / s), and shaping activation (1.8V, 1.5h). After activation, positive electrode material is formed in situ at the positive electrode.

[0049] Example 4 (1) Preparation of precursor: Multi-walled carbon nanotubes, γ-cyclodextrin, XC-72 conductive carbon and polytetrafluoroethylene were mixed in a mass ratio of 82:10:4:4. Isopropanol with a mass of 15 times the total solid mass was added and the mixture was slurried at 800 r / min and 30℃ for 20 min. The mixture was pressed into 0.3 mm thin sheets and dried at room temperature for 2.5 h to obtain the composite precursor cathode. (2) Assemble the battery: Seal the composite precursor as the positive electrode, zinc foil as the negative electrode, microporous membrane as the separator and an electrolyte consisting of a 3 mol / L ZnBr2 aqueous solution and a 1 mol / L urea solution to obtain the assembled battery; (3) In-situ electrochemical activation: A step-by-step electrochemical activation procedure is performed at 30°C, including pre-activation (1.4V, 2h), cyclic activation (1.7V, 10 cycles, scan rate 15mV / s), and shaping activation (1.8V, 0.8h). After activation, positive electrode material is formed in situ at the positive electrode.

[0050] Comparative Example 1 (1) Multi-walled carbon nanotubes were calcined in an ammonia atmosphere for 8 hours at a calcination temperature of 300℃ and then naturally cooled to obtain nitrogen-doped multi-walled carbon nanotubes. (2) Add concentrated nitric acid to the nitrogen-doped multi-walled carbon nanotubes, ultrasonically disperse for 40 min, reflux at 1000 rpm and 80°C for 12 h, filter, wash with sodium hydroxide solution until neutral, wash with deionized water, and dry at 70°C for 10 h to obtain carboxylated nitrogen-doped multi-walled carbon nanotubes. (3) Add cyclodextrin to the carboxylated nitrogen-doped multi-walled carbon nanotubes, ultrasonically disperse for 30 min, stir, filter, wash with ultrapure water, and dry at 60°C for 12 h to obtain cyclodextrin-nitrogen-doped multi-walled carbon nanotubes, which is the cathode material.

[0051] Comparative Example 2 (1) Preparation of precursor: Multi-walled carbon nanotubes, α-cyclodextrin, XC-72 conductive carbon and polytetrafluoroethylene were mixed in a mass ratio of 82:10:4:4. Isopropanol, which was 10 times the total mass of solids, was added and the mixture was slurried at 500 r / min and 23℃ for 40 min. The mixture was then pressed into 0.15 mm thin sheets and dried at room temperature for 2.5 h to obtain the composite precursor cathode. (2) Assemble the battery: Seal the composite precursor as the positive electrode, zinc foil as the negative electrode, microporous membrane as the separator and an electrolyte consisting of a mixture of 1.5 mol / L ZnBr2 aqueous solution and 0.6 mol / L urea to obtain the assembled battery; (3) In-situ electrochemical activation: A step-by-step electrochemical activation procedure is performed at 23°C, including pre-activation (1.5V, 2.5h), cyclic activation (1.8V, 15 cycles, scan rate 8mV / s), and shaping activation (1.95V, 1.5h). After activation, positive electrode material is formed in situ at the positive electrode.

[0052] Comparative Example 3 Cathode preparation: Multi-walled carbon nanotubes, XC-72 conductive carbon, and tetrafluoroethylene were mixed in a mass ratio of 18:1:1, slurry was prepared with isopropanol, dried at room temperature for 3 hours, and cut into 1cm×1cm thin sheets to obtain the cathode material. Battery assembly: positive electrode, zinc foil negative electrode, microporous membrane, 2 mol / L ZnBr2 aqueous solution; Direct charging and discharging.

[0053] Performance testing After all the batteries in the embodiments and comparative examples were assembled according to their respective schemes, they were allowed to stand for 1 hour to stabilize the contact state between the electrolyte and the electrodes before performance testing. The performance test results of the positive electrode materials described in Examples 1-4 and Comparative Examples 1-3 are shown in Table 1 below. Table 1 Performance test results of the cathode materials described in Examples 1-4 and Comparative Examples 1-3 The results show that the charge / discharge voltage difference (10 mA / cm) in Examples 1-4 2 The voltage (262-278mV) is lower than that of the prior art (Comparative Example 1, 281mV), and the energy retention rate after 4 days of rest (73%-81%) is significantly higher than that of Comparative Example 1 (72%). Through the synergistic effect of "in-situ nitrogen doping and cyclodextrin fixation", the core pain points of large charging polarization and severe self-discharge of zinc-bromine static batteries are solved more efficiently; in Example 3, 10mA / cm 2 The voltage difference was only 262mV, and the energy retention rate reached 81%, which is 6.8% lower and 12.5% ​​higher than that of Comparative Example 1, respectively. The performance fluctuations between different examples were small, proving that the method described in this invention has stability. Moreover, compared with Example 1, the parameters in the in-situ electrochemical activation were changed in Comparative Example 1, with a change of 10mA / cm. 2 When the voltage difference rises to 322mV, the energy retention rate drops to 64%, which will lead to electrolyte decomposition and performance degradation.

[0054] In summary, this invention uses multi-walled carbon nanotubes and cyclodextrin nitrogen-containing precursors as composite precursors. After direct assembly into a battery, the process is completed simultaneously inside the battery through a specific electrochemical procedure. Specifically, electrochemical oxidation generates carboxyl groups, the nitrogen-containing precursor is electrochemically decomposed to achieve nitrogen doping, and the carboxyl groups are fixed by in-situ esterification with cyclodextrin hydroxyl groups. Finally, a cyclodextrin-nitrogen-doped multi-walled carbon nanotube cathode material is formed in-situ at the cathode, realizing assembly as preparation and activation as forming.

[0055] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention. The scope of protection of the present invention is determined by the appended claims.

[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing cathode materials through in-situ electrochemical activation, characterized in that, Includes the following steps: (1) Preparation of precursor: Multi-walled carbon nanotubes, cyclodextrin, XC-72 conductive carbon and polytetrafluoroethylene are mixed, isopropanol is added to make a slurry, pressed into a thin sheet, and dried at room temperature to obtain a composite precursor cathode. (2) Assemble the battery: Seal the composite precursor as the positive electrode, zinc foil as the negative electrode, microporous membrane as the separator and electrolyte to obtain the assembled battery; (3) In-situ electrochemical activation: A step-by-step electrochemical activation procedure is performed at room temperature. The step-by-step electrochemical activation includes a first stage, a second stage and a third stage. The first stage is pre-activation, the second stage is cyclic activation, and the third stage is sizing activation. After activation, a positive electrode material is formed in situ at the positive electrode.

2. The method for preparing cathode materials by in-situ electrochemical activation according to claim 1, characterized in that, In step (1), the multi-walled carbon nanotubes, cyclodextrin, XC-72 conductive carbon, and polytetrafluoroethylene are mixed in a mass ratio of 80-85:10-15:3-5:2-5.

3. The method for preparing cathode materials by in-situ electrochemical activation according to claim 1, characterized in that, The cyclodextrin mentioned in step (1) is one or more of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-α-cyclodextrin, hydroxyethyl-β-cyclodextrin, and hydroxypropyl-γ-cyclodextrin.

4. The method for preparing cathode materials by in-situ electrochemical activation according to claim 1, characterized in that, The amount of isopropanol added in step (1) is 8 to 15 times the total mass of solids; the slurry preparation parameters are: rotation speed 400 to 800 r / min, time 20 to 40 min, and temperature 20 to 30 °C.

5. The method for preparing cathode materials by in-situ electrochemical activation according to claim 1, characterized in that, In step (1), the thickness of the sheet is 0.1~0.3mm; the room temperature drying time is 2~4h.

6. The method for preparing cathode materials by in-situ electrochemical activation according to claim 1, characterized in that, The electrolyte in step (2) contains 1-3 mol / L ZnBr2 aqueous solution and 0.5-1 mol / L nitrogen-containing precursor; the nitrogen-containing precursor is urea or melamine.

7. The method for preparing cathode materials by in-situ electrochemical activation according to claim 1, characterized in that, The room temperature mentioned in step (3) is 20~30℃.

8. The method for preparing cathode materials by in-situ electrochemical activation according to claim 1, characterized in that, The pre-activation parameters in step (3) are: potential 1.0~1.4V and time 1.5~4h.

9. The method for preparing cathode materials by in-situ electrochemical activation according to claim 1, characterized in that, The cyclic activation parameters mentioned in step (3) are: potential 0.7~1.7V, number of cycles 8~22, and scan rate 3-15mV / s.

10. The method for preparing cathode materials by in-situ electrochemical activation according to claim 1, characterized in that, The activation parameters in step (3) are: potential 1.7~1.9V and time 0.8~2.5h.

Citation Information

Patent Citations

  • Preparation method and application of zinc-bromine static battery positive electrode material

    CN119764469A